SISTEM INFORMASI PENJUALAN BERBASIS WEBSITE PADA ROTI MRUYUNG GUESTHOUSE & CAFE BANYUMAS - Felix Wahyu Sejati (LPPM Poltek ST Paul, 2025)
Roti Mruyung Guesthouse & Cafe is a business engaged in culinary and lodging services that still faces challenges in its sales system. The management of transaction data, product stock, and sales reports is still carried out manually, while product ordering is conducted through social media such as Instagram and WhatsApp. This condition often leads to data recording errors, slow customer responses, and inefficient recap processes. This study aims to design and develop a web-based sales information system to improve operational efficiency at Roti Mruyung Guesthouse & Cafe. The system development was carried out using the Prototype method with the PHP programming language, Laravel framework, and MySQL database. The resulting system has been tested through Paired Sample t-Test, black box testing, white box testing, and quality evaluation based on the ISO/IEC 25010 standard. The ISO/IEC 25010 testing results showed an average score of 99.5% for Functional Suitability, 92.5% for Performance Efficiency, 93.75% for Usability, and 92.5% for Reliability. Based on these results, it can be concluded that the developed sales information system has good quality, meets user needs, and is able to significantly improve operational efficiency.